ANALISIS PENGARUH RETURN ON ASSET, NET PROFIT MARGIN, EARNING PER SHARE TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Pibrianti Dahlia Lastria Simanjuntak; Raina Linda Sari (Departemen Ekonomi Pembangunan USU, 2014)
This study aims to analyze the influence of Return on Assets (ROA), Net Profit Margin (NPM) and Earnings per Share (EPS) to towards stock return on banking companies listed in Indonesia Stock Exchange. The independence variables in this research are Return on Asset (ROA), Net Profit Margin (NPM), Earning per Share (EPS) and stock return as dependent variable. The samples in this research is 21 banking companies listed in Indonesia Stock Exchange in the study period 2008-2012. The sampling technique used was purposive sampling technique. The analysis technique used in this research is the analysis of panel data (pooled data) by using analytical methods Random Effects Model (REM). The results of this research show that Return on Assets (ROA), Net Profit Margin (NPM) and Earnings per Share (EPS) either partially or simultaneously had no effect to the banking company's stock return are listed on the Indonesia Stock Exchange.Keywords: Return on Asset (ROA), Net Profit Margin (NPM), Earning per Share (EPS) and stock return